Delayed Acetaminophen Absorption Resulting in Acute Liver Failure - Huiling Tan; Paul Stathakis; Benoj Varghese; Nicholas A. Buckley; Angela L. Chiew (Case Reports in Critical Care)
Introduction. Acetaminophen is a common medication involved in deliberate and accidental self-poisoning. The acetaminophen treatment nomogram is used to guide acetylcysteine treatment. It is rare to develop hepatotoxicity with an initial acetaminophen concentration below the nomogram line. We present a case of acetaminophen ingestion with an initial concentration below the nomogram line that developed hepatic failure, due to a delayed peak acetaminophen concentration secondary to coingesting medications that slow gastric emptying. Case Report. A 43-year-old (55 kg) female presented after ingesting an unknown quantity of acetaminophen, clonidine, and alcohol. Her acetaminophen level was 41 mg/L (256 μmol/L) at 4.5 h post-ingestion, well below the nomogram line, and ALT was 25 U/L. Hence, acetylcysteine was not commenced. She was intubated for decreased level of conscious. A repeat acetaminophen level 4 h later was 39 mg/L (242 μmol/L), still below the nomogram line. She was extubated 24 h later.At 38 h post-ingestion she developed abdominal pain, the repeat acetaminophen level was 85 mg/L (560 μmol/L), ALT was 489 U/L, and acetylcysteine was commenced. The patient developed hepatic failure with a peak ALT of 7009 U/L and INR of 7.5 but made a full recovery. It was discovered that she had ingested a combination acetaminophen product containing dextromethorphan and chlorphenamine. Acetaminophen metabolites were measured, including nontoxic glucuronide and sulfate conjugates and toxic cytochrome P450 (CYP) metabolites. The metabolite data demonstrated increasing CYP metabolites in occurrence with the delayed acetaminophen peak concentration. Discussion. Opioids and antimuscarinic agents are known to delay gastric emptying and clonidine may also have contributed. These coingested medications resulted in delayed acetaminophen absorption. This case highlights the issue of altered pharmacokinetics when patients coingest gut slowing agents.